Can noninvasive testing identify benign patterns of suggested pre‐excitation on electrocardiogram?. Issue 7 (21st May 2019) - Robinson, Jeffrey A.; Anderson, Jeffrey B.; Knilans, Timothy K.; Spar, David S.; Czosek, Richard J.
Abstract: Background: The presence of anterograde conduction through an accessory pathway (AP) has been linked to sudden cardiac death. Unfortunately, pre‐excitation associated with classic pathways can be difficult to differentiate from benign APs such as nodofascicular fibers. Objective: Identifying characteristics on electrocardiogram (ECG) and exercise that differentiate classic and benign AP connections in suggested pre‐excitation patterns. Methods: Retrospective review of patients presenting between 1995 and 2017 with ventricular pre‐excitation on ECG, determined to have either typical left‐lateral AP during electrophysiology study (EPS), or benign, or no AP determined by either transesophageal electrophysiology study (TEP), or EPS. Results: A total of 96 patients were included, 14.2 years (4‐24), 45% female, 90% Caucasian. Of these, 60 (63%) had a classic APs identified on EPS and 58 (97%) underwent successful ablation. Conversely, 36 (37%) had benign pathways identified. ECG findings differed between the groups: PR‐interval 102 versus 120 ms ( P < .0001), QRS‐duration 110 versus 102 ms ( P < .0001), QRS‐axis 74 versus 59 degrees ( P = .0005), and QRS onset to peak R/S in limb leads 64 versus 42 ms ( P < .0001), and precordial leads 66 versus 46 ms ( P < .0001). Change in QRS duration during exercise differed between the groups: 25 versus 2 ms ( P < .0001) and ECG characteristics identified the presence of an AP with 97% sensitivity and 94% negative predictive value. Conclusion: Classic and benign APs exhibit different ECG characteristics, though clinical overlap does not allow for absolute differentiation. These data may help with risk stratification decision making though does not obviate the need for additional invasive testing.